(3GdeONd Edi UfGYI GdWHs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3Ef ef GdhGLH Cf fJYQa GdfGaY hfSdcg , hfJYQa GdVGQ hfLGfHg , hfYJfi HCeQ gPG GdHOf GdPi dG TF CbQH Edi fahSfG efg s
(3BNQgG (B:s
(3hbO GfJgjfG ef Gdbhd ai cJGH GdeONd GdPi CdafGg ddeJYdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GfXQg eY GdefUhQi ai GdWH ddQGRi Qbe (B" 781-785"s
(3fXQg eY Qbe (B" 730" (3GdeQTO ddQQGRis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B227 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdWHs